Karakteristik Komposit Serat Enceng Gondok Dengan Fraksi Volume 15%, 20%, 25% Terhadap Uji Bending, Uji Tarik Dan Daya Serap Bunyi Untuk Dinding Peredam Suara - Heri Setyawan, Riyan, Wijianto, ST., M.Eng.Sc, Ir. Pramuko IP, MT (2016)
Purpose of the research is to know tensile strength and bending strength of water hyacinth (eceng gondok) composite at variation of volume fraction of 15%, 20% and 25% with standards of ASTM D 3039 and ASTM D 799-99, andalso, capability of sound absorption with sponge layer and plywood layer and without those layers are also researched with ANSI S1.13-05 standards. Primary material of the research is water hyacinth fiber with polyester matrix of BQTN 157. Main variable of the research is volume fractions of 15%, 20% and 25% fibers with procedure of tensile test referring to ASTM D 3039, the bending test refers to ASTM D 799-9 and the test of sound absorption refers to ANSI S1.13-05. Results of the research indicated that the average highest tensile strength of was found at volume fraction of 25%, namely 131.76 MPa and the lowest one was found at volume fraction of 15%, namely 59.69 MPa and the average highest modulus of elasticity was found at volume fraction of 25%, namely 17989.61 MPa and the lowest one was found at volume fraction of 15%, namely 8149.27 MPA. The average highesttensile strength of 30.41 MPa was found at volume fraction of 25% and the lowest one of 12.43 MPa was found at volume fraction of 15% and the average highest modulus of elasticityof 1265.15 MPa was found at volume fraction of 25% and the lowest one of 996.82 was found at volume fraction of 15%. The highest sound absorption without plywood and plank layers was found at volume fraction of 25%, namely 1.34 dB and the lowest one was found at volume fraction of 15%, namely 0.21 dB. While, the highest value of sound absorption with the use of layers was found at volume fraction of 25%, namely 1.66 dB and the lowest one was found at volume fraction of 15%, namely 0.67 dB.